Mass Media Role of Siamnews Local Newspaper (Chanthaburi) and Perception of the Receivers - สมจินดา, วลัยลักษณ์ (Siam Communication Review, 2017)
This study is both qualitative and quantitative research. It has objective for analyzing contents,studying in mass media role and ethics, and explore perception of the receivers in role and ethics of local mass media, Siamnews newspaper (Chanthaburi). The study conducted by content analysis from 14 issues, in-depth interview with newspaper owner and editor, and survey research by using question as data collection tool from 246 readers. This study could be concluded that; (1) Siamnews local newspaper (Chanthaburi) plays the role of local mass media to serve public by adhering to its ideology of being newspaper for righteousness and justice. For 33 years, there was change of contents which could be divided into 3 eras; Build up era (nurturing of ideology), Adapt era, and Convergence of social and printed media era. Business structure is a single-owned without profit. The owner must allocate other sources of income to support but has no plan to cease operation soon. (2) Study in role and ethics of Siamnews local newspaper found that are in accordance with role and ethics from referenced theories. Additionally, it has other role as social responsibility project for almost 33 years. and (3) Perception of the receivers is in accordance with formal role of newspaper. It gains the most trust from role of glorification for good Samaritan, follow by compliment of local activists and entertainment and information This newspaper has distinguished role and ethics which the receivers have recognized but has regular readers only 7.7%, besides that are seldom readers and have read only 1-2 times. Current social role of this newspaper is unpopular media but firmly adhere in role of good media